2012
DOI: 10.1097/crd.0b013e318259294b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Female Sex on Cardiac Arrhythmias

Abstract: We performed a systematic literature review to examine the effect of female sex on cardiac electrophysiology and arrhythmias. Women have faster resting heart rates yet longer QTc intervals. Women also have shorter PR and QRS intervals; these are presumed to be due to the small heart size of women and hormonal effects on ion channels. Women are two times more likely to experience atrioventricular nodal re-entry tachycardia than men. In contrast to atrioventricular nodal re-entry tachycardia, accessory-pathway-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 140 publications
1
40
0
Order By: Relevance
“…It has been recognized that additional factors contribute to the manifestation of the arrhythmia and the observable symptoms. The impact of factors such as gender, age, seasonal changes, circadian rhythm, and triggers such as auditory stimuli or exercise, or physiological challenges such as hypokalemia have been reported (42,89,152,165,227,290,414,486). Beyond environmental modifiers, the presence of additional genetic modifiers is well-recognized.…”
Section: Striking the Wrong Note: Genetic Variation Causing Arrhytmentioning
confidence: 99%
“…It has been recognized that additional factors contribute to the manifestation of the arrhythmia and the observable symptoms. The impact of factors such as gender, age, seasonal changes, circadian rhythm, and triggers such as auditory stimuli or exercise, or physiological challenges such as hypokalemia have been reported (42,89,152,165,227,290,414,486). Beyond environmental modifiers, the presence of additional genetic modifiers is well-recognized.…”
Section: Striking the Wrong Note: Genetic Variation Causing Arrhytmentioning
confidence: 99%
“…For example, circulating androgens seem to shorten the QT interval and protect against torsades de pointes [4]. After puberty, women with both congenital and acquired long QT syndrome (LQTS) are at higher risk of cardiac events compared with men [3,5].…”
Section: Basic Electrophysiologymentioning
confidence: 99%
“…There is some evidence that the QT interval shortens during the luteal phase, which occurs after ovulation when oestrogen levels are lowest and progesterone levels highest. These basic electrophysiological differences have direct clinical correlations [3]. For example, circulating androgens seem to shorten the QT interval and protect against torsades de pointes [4].…”
Section: Basic Electrophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that there are important differences between males and females in the clinical characteristics of many cardiovascular diseases, which are also extended for rhythm and conduction disturbances, due to various hormonal and constitutional differences. [32][33][34] The effects of sex hormones on the conductibility and excitability of the heart vary between genders, as testosterone leads to a shortening of the QT interval, while estrogen leads to an elongation of the QT interval. 35 A study on 5,116 patients found that the resting heart rate of female patients is higher with up to 3-5 beats per minute.…”
Section: Discussionmentioning
confidence: 99%